1999
DOI: 10.1182/blood.v94.9.3101.421k04_3101_3107
|View full text |Cite
|
Sign up to set email alerts
|

Reduced NFAT1 Protein Expression in Human Umbilical Cord Blood T Lymphocytes

Abstract: Umbilical cord blood (UCB) stem cells from related and unrelated allogeneic donors have emerged as novel treatment for patients with hematologic malignancies. The incidence and severity of acute graft-versus-host disease (GVHD) after UCB transplantation compares favorably with that observed in recipients of matched unrelated donor allogeneic grafts, but remains a major cause of morbidity and mortality. It has been shown that stimulated lymphocytes from UCB have reduced production of cytokines including interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…[38][39][40] NFAT promotes PD-1 expression in early activated CD81 T cells in adults; therefore, unbalanced NFAT signaling may contribute to T-cell anergy. 16,41 Interestingly, our activated CD81 CB T cells did not express PD-1, maybe due to impaired NFAT signaling, but this should be analyzed in the future. Wei and colleagues 42 demonstrated that various T-cell effector functions show differential susceptibility to PD-1 signaling and that already low levels of PD-1 can inhibit T-cell expansion as well as IL-2 and TNFa production.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[38][39][40] NFAT promotes PD-1 expression in early activated CD81 T cells in adults; therefore, unbalanced NFAT signaling may contribute to T-cell anergy. 16,41 Interestingly, our activated CD81 CB T cells did not express PD-1, maybe due to impaired NFAT signaling, but this should be analyzed in the future. Wei and colleagues 42 demonstrated that various T-cell effector functions show differential susceptibility to PD-1 signaling and that already low levels of PD-1 can inhibit T-cell expansion as well as IL-2 and TNFa production.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12][13][14] Furthermore, CB T cells are characterized by impaired nuclear factor of activated T cells (NFAT) signaling and reduced reactivity. [15][16][17] Further investigation is needed to gain a thorough understanding of the na€ ıvet e of CB immune cells and the interplay with recipient target T cells in the context of GVHD and GVT effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contain high concentrations of TRECs [10,11] High cell turn-over [10][11][12][13][14] Have high constitutive telomerase activity and long telomeric sequences [10] Have increased susceptibility to apoptosis, prevented by cytokines signalling through the IL-2 receptor g -chain [11,14,16] Proliferation induced by IL-7 and IL-15 [10,11,13,14,16,17,19,20] Low production of IFN-g by CD4 T lymphocytes associated with hypermethylation of IFN-g promoter [25,26,28] Expression of CD40 ligand by CD4 T lymphocytes is controversial [29][30][31][32][33][34][35] Expression of NFAT by CD4 T lymphocytes is controversial [36][37][38] CD25 + regulatory T lymphocytes occur spontaneously during foetal life [41][42][43][44] and previously been proposed as a marker of recent thymic emigrants [40]. Essential regulatory mechanisms controlling T cell responses are in place in early life.…”
Section: Referencesmentioning
confidence: 99%
“…These studies have been echoed by studies in the human neonate that demonstrated a predisposition towards Th2 cytokine production in response to stimulation with allergens (Prescott et al, 1998). Recently, absence of expression of nuclear factor of activated T-cell transcription factor (NFAT)-1, a critical regulator of cytokine gene expression, in human cord blood T cells has been considered as a basis for diminished GVHD (Kadereit et al, 1999). Thus, the elucidation of the role of constitutive cytokine production by cord blood compared with adult-derived T cells in the mediation of GVHD remains an important goal in stem cell transplantation immunology.…”
mentioning
confidence: 99%